Relation of the research indicators of the university rankings and the measurement of scientific production in Open Access (LACCEI, 2024)
The evolution of university rankings over the years has been characterized by trying to respond to the shortcomings of their measurement systems and guiding the choice of students and academics in search of quality in teaching and research. where it seems that the rankings have outlined strategic lines aimed at meeting various objectives, including improving the accuracy of their indicators and expanding the measurements to other activities carried out by universities, however there are few indicators that promote or measure the open access of this research resources. The objective of this work is to identify the importance of the indicators of the university rankings related to the measurement and visibility of open access publications and to compare the coverage of the sources used in these indicators with other open access platforms used by academic institutions and research in Panama. The results obtained indicate that of the six rankings evaluated, only two use indicators that measure open access, but only one gives a percentage of barely 2% to this indicator, on the other hand, when making a comparison of the coverage of the fonts used. Through the ranking of universities and other open access platforms, it is identified that the open access platforms have greater coverage of publications where they almost double the number of integrated documents from Panamanian institutions in some cases and in some cases greater impact through citations.